Nuclear Medicine A Guide for Healthcare Professionals and Patients - Prakash, Dibya (Springer India : Imprint: Springer, 2014)
The book is a compilation of guidelines from various organizations such as Society of Nuclear Medicine & Molecular Imaging, European Association of Nuclear Medicine, American College of Radiology, and International Atomic Energy Agency. The description of the procedures is simple, easy to understand and current. The aim of this book is: a) Nuclear medicine professionals can use this book as a quick reference about how a procedure is to be performed. The set of instructions given to a patient before, during and after the procedure have also been included in each chapter. b) To educate general physicians about nuclear medicine procedures. The procedures are explained briefly with common indications and precautions. Normal and abnormal nuclear medicine images have also been included for quick comparison. c) To educate paramedical staff or healthcare professionals so that they can brace themselves rather than embrace. By this they can clarify, suffice the eager and send patients to a nuclear medicine department after proper preparation. d) To educate patients who come for nuclear medicine procedure. e) To remove apprehensions and doubts which arise in the mind of the patients.